2021
DOI: 10.1007/s00426-021-01490-w
|View full text |Cite
|
Sign up to set email alerts
|

A dimensional measure of safety behavior: A non-dichotomous assessment of costly avoidance in human fear conditioning

Abstract: Safety behavior prevents the occurrence of threat, thus it is typically considered adaptive. However, safety behavior in anxiety-related disorders is often costly, and persists even the situation does not entail realistic threat. Individuals can engage in safety behavior to varying extents, however, these behaviors are typically measured dichotomously (i.e., to execute or not). To better understand the nuances of safety behavior, this study developed a dimensional measure of safety behavior that had a negative… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 62 publications
7
19
0
Order By: Relevance
“…These results are consistent with the idea that the subjective motivational value associated with the action outcome is a crucial determinant of instrumental avoidance (Pittig et al, 2020). In line with this, a recent study has shown that the more a stimulus predicting a CS+ acquired negative valence throughout the task, the stronger the CS-avoidance (Wong & Pittig, 2021). We also observed that response repetition after avoidance feedback (often labelled win-stay) and switch after approach feedback (lose-shift) correlated with both the learning rate and the weighting parameter, confirming that win-stay and lose-switch are proxies of individual sensitivity to positive and negative feedback, respectively (Bari et al, 2010;Estes, 1950, p. 195;Paulus et al, 2002;St.…”
Section: Discussionsupporting
confidence: 90%
“…These results are consistent with the idea that the subjective motivational value associated with the action outcome is a crucial determinant of instrumental avoidance (Pittig et al, 2020). In line with this, a recent study has shown that the more a stimulus predicting a CS+ acquired negative valence throughout the task, the stronger the CS-avoidance (Wong & Pittig, 2021). We also observed that response repetition after avoidance feedback (often labelled win-stay) and switch after approach feedback (lose-shift) correlated with both the learning rate and the weighting parameter, confirming that win-stay and lose-switch are proxies of individual sensitivity to positive and negative feedback, respectively (Bari et al, 2010;Estes, 1950, p. 195;Paulus et al, 2002;St.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast to animal studies allowing a comprehensive evaluation of avoidance from subtle to excessive behaviors (117,118), this complex phenomenon is often reduced to simple button presses indicating an evaluative decision to avoid or not to avoid an imminent outcome in human research (46). Attempts to overcome this lack of face validity have been made by including behavioral measures such as eye (119) and motion tracking (120) or by implementing a gradual admission of aversive outcomes (121).…”
Section: Challenges In Experimental Research On Avoidancementioning
confidence: 99%
“…Overall, EPP fear conditioning research has started to adopt more transdiagnostic and dimensional approaches to psychopathology. Examples include a transdiagnostic approaches examining fear conditioning across fear-related disorders [41,42], as well as dimensional approaches with respect to self-reported symptoms [43][44][45][46], or to avoidance behaviors [47,48].…”
Section: Sample Selection: Insights From Rdoc Approaches To Improve E...mentioning
confidence: 99%